Los argumentos de Orosio en la polémica pagano-cristiana - Martínez Cavero, Pedro (Antigüedad y Cristianismo, 1990)
In his HISTORY, Orosius attacks the pagans, developing some arguments that we study here. He compiles from other author’s works the misfortunes that took place in history and compares them with the ones of his time, affirming that the former are seen as less grave for having become literary topics. He rests importance to the fall of Rome in 410 and fills the narration with providential facts. He also defends the antiquity and universality of Christianity, as well as the unity of the history of all the humanity, which he articulates around the theory of the four Monarchies of Daniel. The Roman Republic is deprived of its myth but he appraises Augustus’monarchy, integrating some pagan concepts in the Christian vision of history. He finally demonstrates that Christianity is not the cause of the decadence of Rome because the Empire itself is the product of Christianity.